Sosialisasi Keuangan Digital Peer-To-Peer Lending (P2P) Terhadap Pelaku UMKM Di Desa Padangsambian Klod - I Putu Satria Parayangan; Komang Widhya Sedana Putra P; I Putu Dharmawan Pradhana; Nyoman Sri Manik Parasari (Yayasan Inspirasi El Burhani, 2025)
Introduction: The success of MSMEs depends on financial literacy and problem-solving skills. However, many MSME owners in Desa Padangsambian Klod lack knowledge of financial management and Fintech P2P Lending, making them vulnerable to illegal online loans with high interest rates and unethical collection practices. Objective: This engagement intends to increase knowledge of the digital financial services available to MSMEs in Desa Padangsambian Klod by teaching them the nuances of what is involved in Fintech P2P Lending. The community seeks assistance from external sources in enabling them to increase their capital while decreasing the chances of becoming a victim of illegal online lending. Method: Socialization of the program was done on a face-to-face basis by going from one MSME owner to another. This method provided an opportunity for every MSME to receive focused education that addressed their individual challenges. Result: Knowledge was acquired by the participants concerning the distinctions between legal and illegal P2P Lending platforms, the dangers that stemmed from illegal lending practices, and how to choose a safe and licensed platform. Conclusion: There is a great need for financial literacy for MSMEs which would enable them to sober up to unscrupulous financial dealings. More initiatives have to be put into place in order to assist MSMEs to cope up with the changing environment in financing that is dominated by the digital world.